COMPARATIVE EFFECTS OF THYMOGEN AND THYMALIN UPON IMMUNITY, HAEMOSTASIS AND POSTOPERATIVE ENDOMETRITIS - L. I. Anokhova; E. D. Zagorodnaya; A. V. Pateyuk; B. I. Kuznik (Медицинская иммунология, 2014)
Abstract.  An  immune  deficiency  state,  along  with  continuously  increased  intravascular  coagulation, are  shown  to  develop  in  puerperal  women  after  Caesarian  section  complicated  by  endometritis.  Complex therapeutic schedules aimed for endometritis treatment, including thymic peptides (thymalin or thymogen) are accompanied by more rapid correction of these disorders and favorable clinical effect. (Med. Immunol., 2011,  vol. 13, N 2-3, pp 279-284)